Pengaruh variasi Tekanan dan level air tangki Hydrophore terhadap laju aliran massa pada sistem distribusi air tawar - Susanto -; Gunawan Budi Santoso; Yulius Oscar; Wahyu Ari Putranto; Widar Bayu Wantoro (Universitas Muhammadiyah Metro, 2026)
The paper is The performance of water distribution in buildings is strongly influenced by the relative position of the reservoir and the outlet pipe. This represents an important technology transfer for enhancing building services engineering. This study examines the performance of a hydrophore system under variations in pipe height, water level, and tank pressure. Experiments were conducted using pipe heights of 1, 2, and 3 meters; water levels of ¼, ½, and ¾ of the tank capacity; and tank pressures of 1, 2, and 3 bar. Pressure adjustments were made by adding or releasing compressed air. System performance was evaluated by measuring the mass flow rate through one, two, and three outlet pipes operated individually and simultaneously. The highest mass flow rate for a single outlet pipe was achieved at a ½ water level and 3 bar pressure, yielding 67.87 kg/min through outlet pipe 2. For two outlet pipes, the maximum values were obtained at a ¼ water level and 3 bar, producing 72.75 and 73.25 kg/min. With all three outlets open, the highest flow rate reached 79.69 kg/min at a ½ water level and 3 bar. Overall, water level, tank pressure, pipe height, and the number of open outlets significantly affect distribution performance and must be considered in system design for multi-level buildings